THE EFFECTIVENESS OF THE EDUCATION SYSTEM IN THE IMPLEMENTATION OF STATE YOUTH POLICY IN THE COUNTRIES OF CENTRAL ASIA AND THE REFORMS BEING IMPLEMENTED IN THIS DIRECTION - M.H. Abdirasulov (Scholar Express Journal, 2024)
The article examines and analyzes the ongoing reforms in the field of state youth policy and the priorities of state policy, their essence, necessity and significance. The role of the education system in the implementation of state youth policy and reforms implemented in this direction is comparatively analyzed.
Keywords: State policy on youth; youth; education; priority directions of state policy